Qualidade de vida e autoestima em idosas submetidas e não submetidas à cirurgia estética - Pacheco, Lenise Maria Spadoni (2018)
Introduction: the reality of the aging in population got in to plastic surgery field increasing the number of elderly searching for aesthetic surgery. The number of aesthetic surgeries have grown in the last years revealing that self image care is growing too. It is known that aesthetic surgery final objective is to improve quality of life, restoring form and function of that part of the body, bringing self esteem change. Objective: to check the importance of aesthetic surgery for the elderly and if exist quality of life and self esteem difference between elderly women that had aesthetic surgery and that had not. Method: descriptive research, and casecontrol approach with 25 women with age 60 or more who underwent aesthetic surgery and another group of 25 elderly women who did not, paired by socioeconomic data. The used outcomes instruments were: cognitive test MEEM, quality of life questionnaire WHOQoLbref, Rosenberg’s self esteem scale, and a elaborated questionnaire, all filled by the researcher. The results were analised by STATA -version 14.0 and realized Shapiro-Wilk test with average and standart deviation, and qualitative ones with absolute and relative frequency. Results: overall it was identified and age media of 67,26 years, school years average of 9,96 years and the majority had no partner. Substantial comorbidities were hypertension and dyslipidemia. The most realized surgeries were abdominoplasty and blefaroplasty. Motivation mainly were physical discomfort, desire of quality of life improvement and dissatisfaction with self image. Satisfaction level with aesthetic surgery was high when related with their own body and social life. None of them had low self esteem. No difference was found of quality of life and self esteem between the two groups. There was no correlation between aging and self esteem or the different areas of quality of life. Conclusion: the elderly motivation to do aesthetic surgery are physical and psycological. There was no difference of QoL and self esteem between elderly women who had and who had not aesthetic surgery. However, separate analysis of the group who had aesthetic surgery, proved high levels of satisfaction in personal and social life.